Does the systemic administration of l-arginine affect dental implant stability in nicotine consumer dogs? - Bijan Movahedian; Mansour Rismanchian; Hooman Navaei; Saeid Tavanafar; Soheil Koushaei (SpringerOpen, 2021)
Abstract Background Nicotine can have detrimental effects on dental implant osseointegration. This study aimed to evaluate the influence of systemic l-arginine supplement on the osseointegration of dental implants in nicotine consumer dogs. Methods Twelve 1-year Labrador Retriever dogs had their right and left third and fourth mandibular premolars removed, and the sockets were left to heal for 6 months. Dogs were randomly divided into three groups (n = 16): group 1-0.2 mg/kg nicotine was injected twice daily; group 2-0.2 mg/kg nicotine was injected twice daily in addition to 200 mg/kg l-arginine capsules taken orally; and group 3-placebo. Forty-eight dental implants were inserted into the healed sockets of the dog's mandible and were assessed by implant stability quotient (ISQ) using resonance frequency analysis (RFA) during 4 weeks and insertion and removal torque value analysis. Results No implant failure occurred during the study period. The change in torque value between insertion and removal was similar in the placebo and nicotine+arginine consumer dogs (p = 0.276), which shows a positive effect of arginine supplementation in nicotine consumers. There was a significant difference in torque value change between nicotine+arginine vs. nicotine consumers (p = 0.049) and placebo vs. nicotine (p = 0.003). After 4 weeks, the placebo had the most significant improvement in torque value (47.0 ± 16.9), followed by nicotine+arginine (25.1 ± 37.8), and the worst torque value was for the nicotine group (− 5.7 ± 24.0) pound per inch. The results show that except in the first week, there are significant differences in ISQ between the groups in different periods. ISQ in all of the groups has reduced at first but then increased over time. At the time of implant placement, insertion torque was significantly higher in the nicotine consumer group than the nicotine+arginine consumer group and placebo group (p = 0.020). Conclusion Arginine supplementation promotes bone healing and implant primary stability by improving dental implant osseointegration biomechanical characteristics.